The Image Of Crime In The Scientific-Fantastic Configuration Of The Future - Lytvynov, Oleksii; Spitsyna, Hanna (Archives of Criminology and Forensic Sciences, 2022)
One of the forms of expression of new knowledge is science fiction, which projects images of evil. The latter is manifested in personal, cultural, social, political, and other contexts, in various manifestations of crime. Simultaneously, crime in science fiction is in a broader and more ambiguous sense than in conventional criminology, although it is correlated with it. It is noted that upon closer examination, the image of an “evil deed” in science fiction belongs to that sphere, which in legal language is designated as “intention”, that is, a planned action. Meanwhile, in the criminal law sense, “intention” does not yet constitute an actual illegal act, but is only one of the stages of committing a crime. Given that a crime still means an act that carries a public danger (a socially dangerous act), what is important is its destructive power, caused by the energy of the criminal, who encroaches on the human person’s right to life, liberty, and so on. It is noted that juvenile “light” crime, caused by immersion in virtual reality both with the help of various narcotics and in the form of new mental illnesses: gambling addiction, Internet addiction, etc., is becoming more and more widespread. As a result, there is a loss of awareness of the gravity of the crime. It is no coincidence that juvenile “light” crime is associated with various manifestations of extremism, devoid of any compromise and, as a result, neglecting the values of social harmony and tolerance.